Specialized human capital, unemployment risk, and the value premium - Stephan Jank (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
To determine whether negative shocks to specialized human capital are priced in the cross section of stock returns, this study measures shocks to industry-specific human capital by employment growth in that industry. In industries in which employment contracts, exposure to the value factor is significantly higher than in industries in which employment expands. Cross-sectional predictive regressions and hedging portfolio returns document that stocks belonging to industries with low employment growth have higher expected returns than stocks belonging to industries with high employment growth. The return premium related to employment growth is pervasive across small, big, and micro stocks, as well as when micro stocks are excluded. The premium cannot be explained by the capital asset pricing model, but the hedging portfolio's payoffs are inversely related to that of the value-minus-growth risk factor.
Keywords: G10; G11; G12; 330